IMPLEMENTASI KEBIJAKAN PENGEMBANGAN DESA WISATA PASIRMULYA KECAMATAN BANJARAN KABUPATEN BANDUNG - Yogi Gumilar Saaeeful Akbar; Bambang Rudiansah; Tubagus Iqbal Alfiansyah; Elvira Aprilla Anzani (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2026)
This study aims to analyze the effectiveness of policy implementation for the development of Pasirmulya Tourism Village, Banjaran Sub-district, Bandung Regency. The research applies George C. Edwards III’s policy implementation model, which consists of four variables: communication, resources, disposition, and bureaucratic structure. A qualitative descriptive method with a case study approach was used, involving observation, interviews, and documentation with local government officials, tourism managers, and community members. The results indicate that the implementation of the tourism village development policy has not been effective. The main obstacles include lack of communication, limited human and financial resources, weak coordination among institutions, and the absence of standardized operational procedures (SOP). To enhance effectiveness, improvements are needed in communication mechanisms, human resource capacity building, and the establishment of an adaptive and collaborative bureaucratic structure